Tuvans’ attitude towards the earth in the Tuvan literature of the 20th–21st centuries - Kuzhuget, Shenne Yu. (The New Research of Tuva, 2023)
The article analyzes the attitude of the Tuvans to the earth. It was changing throughout the 20th–21st centuries. The sources of the research were the most significant Tuvan fiction works published in different years: novels by the classic Tuvan author, the People’s Writer of Tuva M. B. Kenin-Lopsan (“Chylgychynyӊ өө” / “The Yurt of a Horseherd”, 1980; “Kyrgan-avai өpei yry” / “Grandmother’s Lullaby”, 1984; “Azanyӊ bichezi konchug” / “The Younger Imp”, 1989; “Aldyn chүrek” / “The Golden Heart”, 1992; “Chitken urug” / “The Disappeared Girl”, 2000), as well as a work by the People’s Writer of Tuva N. Sh. Kuular (“Muӊgashtatpaan muӊchulbas yr” / “Uninterrupted Cheerful Song”, 2018).In these literary writings, we can find aspects related to interpretations of the earth. They have different features in connection with certain historical events and processes. These aspects can be divided into three major themes: connection with the earth, the theme of the lost earth and new beliefs about the earth.The ethnographer and writer M. B. Kenin-Lopsan represented the beliefs of the Tuvans that the earth is sacred and we should acquire knowledge about it and be connected with it, etc. He also raised issues of fostering a sense of love for native places and of our obligations to homeland. As Kenin-Lopsan demonstrates, the events of the 20th century made the topic of the loss of native lands, forced separation from them and breaking ties especially relevant for the Tuvans.In his novel, N. Sh. Kuular describes the life of the Tuvans in the early 21st century. He covered several issues at once: the topics of the oblivion of native heath, mass migration to Kyzyl, nostalgia for Tuva during foreign trips, fraternal associations of students and acquisition of land by the Tuvans.The article contains quotations from works in the Tuvan language and the author’s translations of them into Russian.
Keywords: Tuvans; concept of culture; native land; Tuvan literature; artistic device; Tuva; history of Tuva